Adult female learners’ perceptions of and experiences with distance education at University of Ghana - Adu-Marfo, A.; Biney, I.; Asamoah, M.K. (Cogent Education, 2024)
This paper highlights adult female learners’ perception and experiences with blended distance education (DE) program in the University of Ghana. It speci fically investigates female students’ experiences with male and female tutors’ tutoring styles, learner support services, the use of educational technology as well as the extent of the gender-inclusive environment created. It throws light on the positive stories regarding the DE program, potential barriers, and panacea from female lens. The study is guided by feminist theory and Larreamendy-Joerns and Leinhardt goals of DE. A qualitative case study and narrative designs were adopted. Data were conveniently collected from 15 female students enrolled on the DE program at the Accra Learning Center. In-depth face-to-face interviews were employed for data collection. Data were analyzed using interpretivist-evaluative narrative approaches. Findings show that gender gaps still exist in using educational technologies for learning; implying that additional technological and tutoring sup port need to be provided to female students. The paper recommends increasing integration of ICT teaching and learning tools into the curriculum of DE to help in building adult females’ digital skills and confidence to enhance their full participa tion in DE.
Research Article
Keywords: adult females in distance education; educational technology; distance learning